Population dynamics of spotted wing drosophila (Drosophila suzukii) in orchards in the Zagreb area : Dinamika populacije octene mušice ploda (Drosophila suzukii) u voćnjacima na području Zagreba - Pajač Živković, Ivana (Array, 2020)
The invasive species Drosophila suzukii (Matsumura, 1931), the spotted wing drosophila, was first recorded in Croatia in 2010. Since then, it has spread on Croatian territory but its presence has not yet been confirmed in the City of Zagreb. In this research population dynamics of D. suzukii was investigated in three orchards in Zagreb (Maksimir, Jelenovac, Zelenjak) in the period from 20th of March to 27th of November 2017. Feeding traps with apple vinegar were used for catching D. suzukii. The flight began in the period from 27th of June to 11th of July and lasted until 27th of November. The total pest catches were 874 specimens (Jelenovac 187, Maksimir 232 and Zelenjak 455). From September to November there was a continuous flight and a large increase in the number of caught flies, suggesting the presence of more overlapping generations. Besides the host plants, the development of the pest in this area is also enabled by suitable climatic conditions. The present population in the City of Zagreb County poses a danger to fruit producers in the Zagreb County. The results of this research are a contribution to better understanding of the population and the spread of the pest in Croatia.